1981
DOI: 10.1073/pnas.78.6.3906
|View full text |Cite
|
Sign up to set email alerts
|

State of hepatitis B virus DNA in hepatocytes of patients with hepatitis B surface antigen-positive and -negative liver diseases.

Abstract: Using the Southern blot technique and cloned hepatitis B virus (HBV) DNA as a probe, we studied the state of HBV DNA in the liver of 13 patients with hepatocellular carcinoma, 17 patients with chronic hepatitis, and 2 patients with acute hepatitis. The hybridization results were compared with the serological and immunohistological data. Integration of HBV DNA in cellular DNA of the liver from patients with hepatocellular carcinoma was demonstrated. In two patients from which tumorous and nontumorous liver tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
131
2

Year Published

1984
1984
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 313 publications
(141 citation statements)
references
References 25 publications
8
131
2
Order By: Relevance
“…34 In the second study, HBV sequences were detected in the liver or serum of anti-HCVpositive/HBsAg-negative patients with a prevalence significantly higher in patients with serum anti-HBc as the only marker of HBV infection than in those with no evidence of serum HBV markers; in this study liver cirrhosis was significantly more frequent in patients with HBV-DNA sequences than in those without. 35 We should also consider that an appreciable number of HBsAg-negative patients with chronic hepatitis or HCC showed clonally integrated HBV-DNA sequences in their liver or tumor tissues [36][37][38][39][40] and that a much higher prevalence of anti-HBc was described in HCV-infected chronic hepatitis patients with HCC than in those without. 41 Our data, which are supported by the observations of other investigators mentioned earlier, allow us to hypothesize that HCV infection blocks all circulating viral expression of HBV replication, but anti-HBc remains in serum and HBV DNA persists in the hepatocytes, resulting in an increased severity of liver disease and a higher risk of developing HCC.…”
Section: Discussionmentioning
confidence: 99%
“…34 In the second study, HBV sequences were detected in the liver or serum of anti-HCVpositive/HBsAg-negative patients with a prevalence significantly higher in patients with serum anti-HBc as the only marker of HBV infection than in those with no evidence of serum HBV markers; in this study liver cirrhosis was significantly more frequent in patients with HBV-DNA sequences than in those without. 35 We should also consider that an appreciable number of HBsAg-negative patients with chronic hepatitis or HCC showed clonally integrated HBV-DNA sequences in their liver or tumor tissues [36][37][38][39][40] and that a much higher prevalence of anti-HBc was described in HCV-infected chronic hepatitis patients with HCC than in those without. 41 Our data, which are supported by the observations of other investigators mentioned earlier, allow us to hypothesize that HCV infection blocks all circulating viral expression of HBV replication, but anti-HBc remains in serum and HBV DNA persists in the hepatocytes, resulting in an increased severity of liver disease and a higher risk of developing HCC.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Tables 2 and 3, despite initial controversies, the identification of HBV genome in the HCC tumors of HBsAg-negative patients has now also been reported in most, although not all, studies conducted in several geographic areas, including Japan. Some studies using Southern blots with an optimized sensitivity 77,78 and PCR 2 have revealed patterns consistent with limited clonal proliferation of the cells containing HBV genomes. 79 HBV-related cis-activation has also been recently reported in an HBsAg-negative, anti-HBc-positive individual with HCC without cirrhosis.…”
Section: The Clinical Impact Of Hbsag-negative Hbv-dna-positive Infecmentioning
confidence: 99%
“…[6][7][8] Since the early 1980s, several studies have reported the detection of HBV DNA in both tumorous and non-tumorous liver tissue of HBsAg-negative HCC patients. 9,10 However, whether occult HBV infection also contributes to the pathogenesis of HCC remains unclear. Previous studies have demonstrated that the incidence of occult HBV infection varies significantly in HCC patients (12-61%).…”
mentioning
confidence: 99%